Strategic human resources management practices are key to small, medium and micro enterprises effectiveness in South Africa - Jealous Sungwa (SA Journal of Human Resource Management)
Orientation: Small, medium and micro enterprises (SMMEs) are prone to failure primarily because of inadequate human resource (HR) procedures despite their reputation for flexibility, closeness to dependable clients, adaptability and adoption of new technologies.